Antecedents of organizational identification: Implication for account representative performance of Corporation X mediated by perceived supervisor support - Siahaan, Ira Theresia; Mustika, Martina Dwi (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
The role of an Account Representative in Corporation X involved providing a financial income plan in the employment sector, and their performance was evaluated based on specific targets and actual achievement. However, the number of workers in Indonesia who are registered and actively paid could have been higher than the total workforce in the country. Questionnaires were used to collect responses from 160 participants, and the analysis was done using Jamovi version 2.3.28 with Moderated Mediation modules to examine the relationship. The finding suggested that perceived supervisor support significantly influenced the relationship between organizational identification and Account Representatives’ performance, with a 35.3% effect size.